The Effect of Marketing Mix on Revisit Intention at Sijunjung Traditional Village Tourism Destinations - Arfan Zaky Wiadri; Susi Evanita (Marketing Management Studies, 2023)
The purpose of this study was to analyze the effect of the marketing mix on revisit intention at the Sijunjung traditional village tourist attraction. The population in this study that had been determined were visitors who had stayed at the Sijunjung traditional village homestay and the number of samples in this study were 240 people. Data collection uses a questionnaire and is processed with SmartPLS software. The results of this study indicate that: (1) there is a significant influence on marketing mix consisting of product, price, location, promotion, people, process and physical evidence on revisit intention, which is if the product, price, location, promotion, people, process and physical evidence which is a dimension of the marketing mix is ​​getting better, it will increase revisit intention.